Out-of-Hospital Research in the Era of Electronic Health Records. (3rd September 2018) - Newgard, Craig D.; Fu, Rochelle; Malveau, Susan; Rea, Tom; Griffiths, Denise E.; Bulger, Eileen; Klotz, Pat; Tirrell, Abbie; Zive, Dana
Abstract: Conducting out-of-hospital research is unique and challenging and requires tracking patients across multiple phases of care, using multiple sources of patient records and multiple hospitals. The logistics and strategies used for out-of-hospital research are distinct from other forms of clinical research. The increasing use of electronic health records (EHRs) by hospitals and emergency medical services (EMS) agencies presents a large opportunity for accelerating out-of-hospital research, as well as particular challenges. In this study, we describe seven key aspects of designing and implementing out-of-hospital research in the era of EHRs: (1) selection of research sites, (2) defining the patient population, (3) patient sampling and sample size calculations, (4) EMS data, (5) hospital selection, (6) handling missing data, and (7) statistical analysis. We use examples from a recent prospective out-of-hospital cohort study to illustrate these topics, including lessons learned.